З історії розвитку сільської кооперації в Польщі: тенденції 1990-2000-х років - Селіванова-Зеркаль, І.О. (Історичний архів. Наукові студії, 2015)
Шлях здобуття незалежності та створення ефективних форм сільськогосподарських кооперативних утворень Польщі продемонстрували можливість швидкої і конкурентоспроможної трансформації соціалістичної системи господарювання, політичного інтегрування суспільства в ринкову загальноєвропейську економіку. Авторка на основі статистичних та нормативно-правових документів здійснила спробу узагальнити досвід польських кооперативів в сільському господарстві та визначити закономірності, тенденції та історичні особливості. Путь обретения независимости и создания эффективных форм сельскохозяйственных кооперативных образований Польши продемонстрировали возможность быстрой и конкурентоспособной трансформации социалистической системы хозяйствования, политического преобразования общества и интеграция в рыночную общеевропейскую экономику. Автор на основе статистических и нормативно-правовых документов осуществила попытку обобщить опыт польских кооперативов в сельском хозяйстве и определить закономерности, тенденции и исторические особенности. Path independence and the establishment of effective forms of agricultural cooperative education Poland demonstrated quick and competitive transformation of the socialist economic system, the political transformation of society and integration into the European economy market. In terms of scientific and theoretical study of foreign cooperative experience will enable the objective to detect patterns and certain features of its development, it is important to understand the historical process as a whole. From a practical point of importance is the possibility of using the experience to find effective ways to reform and overcome the crisis in agriculture in Ukraine are conditioned not only holding ATO, as well as underlying economic processes.
The purpose of the study is that by analyzing statistical information, government documents published sources, periodicals highlight the complex forms, methods of implementation and practice implementation of agricultural cooperatives in Poland in the years 1990-2000, the period of transition from a socialist to a market economy. The acquired knowledge should not try to mechanically move on Ukrainian soil, be sure to take into account the specifics of national history, psychology and ethnic mentality and only then create your own model using the potential of the cooperative movement as a carrier of patriotic ideas and the way to forming a national community conscious of solid patriotic principles. Author chosen topic has not yet been the object of special scientific study. Therefore there is a need in its development from the Polish government documents and published sources with the latest approaches to research. Agricultural transformation in Poland took place on fundamentally different principles than many post-socialist countries. Since the 1970s, the Polish government pursued a deliberate policy to increase private farms. Therefore, in 1990 adopted the Law on land not turn brought the country’s protest and social tensions. Special development came cooperative movement.
Poland has gained exceptional experience of effective cooperation. Implementation here almost every innovation in the organization of agrarian economy began to implement a series of pilot projects and following extensive propaganda received positive learning experience and on this basis all concerned. Thus, the protection and use of the environment
are considered an integral connection with issues of agricultural economy that includes fisheries, marine products, forestry and forestry raw materials.
Polish historical experience has shown that the main engine of economic growth with the integration of agricultural production should be no large and numerous private equity or commodity agricultural enterprises, and small number of mutual cooperatives, which experience can learn the results of a Polish peasants and Ukrainian during the introduction of the NEP in the 20 years of the twentieth century. Mobility, interest in their activities, participate in the distribution of profits, strategy development, government support as local, regional, national and European level were key to the rapid integration of Polish peasants in the global market economy.